Real-world analysis of strategies to prevent thrombosis and bleeding in adults with ALL treated with asparaginase - Joseph F. Mort; David Brighton; Benjamin Mautner; Eric Pierce; Farid Ghamsari; Cecily Allen; Darren D’Souza; Imari Patel; Justin Lawson; Clayton Jackson; Karin Abernathy; Bradley Yelvington; et al. (Blood Vessels, Thrombosis & Hemostasis)
Abstract: The prognosis of adult patients with acute lymphoblastic leukemia (ALL) has improved with the incorporation of pediatric-inspired regimens that contain PEGylated asparaginase (PEG-Asp). However, PEG-Asp administration is associated with an increased rate of thrombosis. Data regarding the benefits of antithrombin (AT) repletion and prophylactic anticoagulation in adults receiving PEG-Asp–based regimens are limited. We performed a retrospective study to evaluate the rates of induction thrombosis and bleeding among adults receiving ALL therapy containing Asp at 6 academic centers in the United States. Of 233 patients who met the inclusion criteria, 98.3% received PEG-Asp. Ninety-six patients (41.2%) had their AT levels monitored, 58 patients (24.9%) received AT repletion, and 41 patients (17.6%) received prophylactic anticoagulation. Thirty-two patients (13.7%) experienced thrombotic events, with half (53.1%) being line-associated thromboses. In multivariate analysis, the odds of thrombosis did not differ between patients who received AT monitoring, AT repletion, or prophylactic anticoagulation. The odds of thrombosis were 4 times higher for patients with peripherally inserted central catheters than for those with other types of central lines (odds ratio, 4.112; 95% confidence interval, 1.622-10.427; P = .01). Thrombotic risk did not differ based on age, cumulative Asp dose, type of steroid administered, or whether transfusions were performed. Bleeding occurred in 12 patients (5.2%), and major bleeding occurred in 8 patients (3.4%). The odds of bleeding did not increase in the patients who received prophylactic anticoagulation. Our study brings into question whether prophylactic AT repletion and anticoagulation are beneficial strategies for reducing PEG-Asp–associated thrombosis, and large randomized prospective studies are needed.